In vitro anti-proliferative and antioxidant activites of chloroform extract of christia vespertilionis on mcf 7 and mda-mb-231 breast cancer cells - Rofiee, Mohd Salleh; Kek, Teh Lay; Salleh, Mohd Zaki (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
Cancer continues to be a formidable adversary in global public health, exacting a devastating toll on millions of lives each year. Among the most prevalent forms of cancer, breast cancer stands out as a significant contributor to mortality rates worldwide. Despite considerable advancements in medical science and the development of various treatment modalities such as chemotherapy and radiotherapy, these interventions often bring about debilitating side effects, ranging from nausea and fatigue to hair loss. Consequently, there has been a growing interest in exploring alternative and complementary therapies, including herbal medicines, for their potential anticancer properties. One such herbal remedy under investigation is Christia vespertilionis (L.f.) Bakh. F, commonly referred to as "Daun Rerama" or "Butterfly wing" in Malaysia due to the shape of its leaves. Traditionally, C. vespertilionis has been used to treat various ailments, including tuberculosis, snakebites, bronchitis, and muscle weakness, among others. Recent scientific studies have delved into the pharmacological properties of C. vespertilionis, revealing its potential as an anticancer agent. The present study aimed to investigate the cytotoxic properties of C. vespertilionis extract against breast cancer cell lines, particularly estrogen receptor- positive (MCF7) and estrogen receptor-negative (MDA-MB-231) cells. Additionally, the study sought to explore the antioxidant properties of the extract, considering the crucial role of oxidative stress in cancer development and progression. The research methodology involved the extraction of C. vespertilionis leaves using chloroform, followed by phytochemical screening to identify bioactive compounds present in the extract. Flavonoids and saponin were among the compounds detected, indicating the potential pharmacological significance of the plant. Further analysis quantified the total phenolic and flavonoid contents of the extract, providing insights into its antioxidant capacity. Subsequently, the antiproliferative effects of the C. vespertilionis extract were evaluated using the MTT assay, a widely used method for assessing cell viability and proliferation. The results revealed a concentration-dependent cytotoxic effect of the extract on both MCF7 and MDA-MB-231 breast cancer cell lines, with decreasing IC50 values observed over time. While the potency of the extract was lower compared to the standard anticancer drug tamoxifen, the findings underscored the potential of C. vespertilionis as a natural therapeutic agent against breast cancer. Overall, the study sheds light on the promising anticancer properties of C. vespertilionis and highlights the need for further research to elucidate its mechanisms of action and potential clinical applications. Additionally, the findings contribute to the growing body of evidence supporting the use of herbal medicines as adjunctive or alternative therapies in cancer treatment, emphasizing the importance of exploring nature's pharmacopeia in the fight against cancer